2012 ASEE Annual Conference &Amp; Exposition Proceedings
DOI: 10.18260/1-2--21621
|View full text |Cite
|
Sign up to set email alerts
|

Is the Engineering Education Community Becoming More Interdisciplinary?

Abstract: NSF and several private foundations fund his research. His research and teaching focuses on policy of P-12 engineering, how to support teachers and students' academic achievements through engineering learning, the measurement and support of change of habits of mind, particularly in regards to sustainability and the use of cyber-infrastructure to sensitively and resourcefully provide access to and support learning of complexity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 25 publications
0
2
0
Order By: Relevance
“…In addition to the human-curated studies mentioned above, recent developments in big-data analysis have led to a growing number of machine-curated bibliometric studies [12,13] which demonstrate the potential of computational analysis in the field of EER. The big data analysis confirmed the presence of silos [13].…”
Section: A Previous Work Using Bibliometric Analysismentioning
confidence: 99%
“…In addition to the human-curated studies mentioned above, recent developments in big-data analysis have led to a growing number of machine-curated bibliometric studies [12,13] which demonstrate the potential of computational analysis in the field of EER. The big data analysis confirmed the presence of silos [13].…”
Section: A Previous Work Using Bibliometric Analysismentioning
confidence: 99%
“…7,[12][13][14] One study in particular used scientometrics to investigate the interdisciplinary changes in EER through co-authorship collaboration. 15 Findings from this study revealed an increasingly high degree of disciplinarily diversity in EER related articles.…”
Section: Introductionmentioning
confidence: 74%